Fragmentation of Suberin and Composition of Aliphatic Monomers Released by Methanolysis of Cork from Quercus suber L.,Analysed by GC-MS, SEC and MALDI-MS - Bento, M. F.; Pereira, H.; Cunha, M. Á; Moutinho, A. M. C.; van den Berg, K. J.; Boon, J. J.; van den Brink, O.; Heeren, R. M. A. (Holzforschung, 2005)
Suberin from extractive-free cork from Quercus suber L. was depolymerised by methanolysis using different sodium methanolate (NaOMe) concentrations. 1% and 3% NaOMe completely removed suberin from cork (54%–56% of extractive-free cork), but for lower concentrations there was incomplete solubilisation; with 0.05% NaOMe, only approximately 80% of total suberin was removed. The monomeric composition of the extracts differed significantly: for the 0.05% NaOMe, only alkanoic acids and diacids were found; the yield of v-hydroxy acids increased with reactant concentration, as well as alkanols and ferulic acid. Results from light scattering, SEC and MALDI-MS showed that soluble oligomeric fragments containing suberinic acids were present in the methanolysis mixture. The molecular weight of these oligomeric fragments decreased with higher sodium methanolate concentrations.
Keywords: Cork; MALDI-MS; Methanolysis; Quercus suber L.; SEC; Suberin fragmentation

Quality characterization of wine cork stoppers using computer vision - Costa, A.; Pereira, H. (JOURNAL INTERNATIONAL DES SCIENCES DE LA VIGNE ET DU VIN, 2005)
Image analysis techniques were applied on the surface of wine cork stoppers (tops and lateral cylindrical surface) of seven commercial quality classes to characterize their porosity. An increasing trend from the best to the worst quality classes was found for features related to area of pores (i.e. maximum length and width or pore maximum area) and concentration variables (i.e. porosity coefficient or number of pores per 100 cm(2)). Shape variables were rather constant and mean values showed no differences between quality classes. Variation of the pores characteristics within each quality class was large especially in the mid-quality range. Therefore there were no statistically significant differences to allow the isolation of the all quality classes and overlapping was particularly important in the medium-quality classes. The reduction of grading into only three quality classes allowed to isolate statistically different subsets based on porosity coefficient and number of pores per 100 cm(2). These variables can be selected for further development into quality grades specification of wine cork stoppers.
The following values have no corresponding Zotero field: pub-location: 42 RUE MARSAN, 33300 BORDEAUX, FRANCE publisher: VIGNE ET VIN PUBLICATIONS INT
Keywords: computer imaging; quality classes; wine cork stoppers

The effect of cork-stripping damage on diameter growth of Quercus suber L. - Costa, A.; Pereira, H.; Oliveira, A. (Forestry, 2004)
The Mediterranean cork oak (Quercus suber L.) agro-forestry system is oriented towards cork production, with cork being extracted from tree stem and branches as planks by cutting with an axe and stripping off. The effect of damage to the tree during cork stripping was studied in cork oaks, weakened by wounding, by following the diameter growth and its seasonality during a 9-year production cycle, and comparing them with healthy cork oaks. Tree wounding decreased diameter growth during the following cycle, e.g. 8.5 mm a−1 and 9.8 mm a−1 for weakened and healthy trees, respectively, mostly in the 2 years immediately following the cork stripping. The beginning of annual growth in spring and the occurrence of the highest increments in June–August were delayed by about 1 month in the weakened trees. The cork produced by weakened trees was reduced by 13 per cent in thickness, with average cork ring widths of 3.3 mm a−1 vs. 3.8 mm a−1 for healthy trees.
10.1093/forestry/77.1.110.1093/forestry/77.1.1
Keywords: Cork Production; stripping; wound responses (PG)

A dendroclimatological approach to diameter growth in adult cork-oak trees under production - Costa, A.; Pereira, H.; Oliveira, A. (Trees, 2001)
The diameter growth of mature cork oaks under cork production in southwestern Portugal was studied during a 9-year cork-production cycle in relation to fluctuations in precipitation and temperature, and to drought indices combining the two variables. A dendroclimatological approach was applied to the series of 8 complete years contained in the cork-production cycle and growth effects were removed by standardization and calculation of annual growth indices. The most important factor positively influencing diameter growth was cumulative precipitation in the growing season (January–June) and in the previous autumn and winter (October/November of the previous year–June). The monthly temperature is a less influential factor, negatively correlated with diameter growth in high summer drought (August) and positively correlated at the beginning of physiological activity (March).
Keywords: climatic fluctuations; dendroclimatology; diameter growth; Mediterranean climate; Quercus suber L.

The effect of cork removal on the radial growth and phenology of young cork oak trees - Fialho, C.; Lopes, F.; Pereira, H. (Forest Ecology and Management, 2001)
The effect of the removal of cork was studied in 11-years old cork oak trees (Quercus suber L.), growing in favorable conditions, in relation to phenology and radial growth during two years. Longevity of leaves was 14±15 months (1996, 1998) and 10 months (1997). Bud burst started in mid-February and leaf ¯ushing in April, extending until June. Neither a distinct two-period ¯ushing nor an autumn bud burst or leaf ¯ushing were observed. Radial growth started in mid-April and continued until the end of November, with the maximum growth in June and July. In trees with the removal of cork, leaf abscission occurred a little earlier and new branches had on average 23% fewer new leaves. The radial growth of the trees and its general seasonal pattern were not affected by cork removal in the year of removal or in the year after. The only observation was a shift of the maximum radial growth rate from June to July for the trees where cork had been removed
Keywords: cork removal; cork-oak; Phenology; Quercus suber; Radial growth

Characterization of cork growth and quality in one region of production. - Ferreira, A.; Lopes, F.; Pereira, H. (ANNALS OF FOREST SCIENCE, 2000)
Cork growth and quality were characterised in 5 cork oak stands within the production area of the Sado basin (Alcacer do Sal, Portugal) based on a field sampling on 40 trees/stand. Cork thickness was on average 33.8 mm, with 75% of the samples in the commercial classes above 27 mm suitable for production of stoppers. Porosity measured by image analysis was 4.6% on average. Between toe and between stand variability of cork quality was large. The annual average cork growth for a production cycle with 8 complete growth years was 4.1 mm, being highest during the years following cork extraction and decreasing during the cycle. For this region, a production cycle of 9 years is adequate for raw-material industrial requirements. The results show the importance of between tree variability in growth and especially in quality.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75724 PARIS CEDEX 15, FRANCE publisher: EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER
Keywords: Cork; Growth; Porosity; Quality; variability

Thermally assisted transmethylation gas chromatography–mass spectrometry of suberin components in cork from Quercus suber L. - Bento, M. F.; Pereira, H. (Phytochemical Analysis, 1998)
Thermally assisted transmethylation gas chromatography - mass spectrometry with tetramethylammonium hydroxide has been applied for the qualitative and quantitative analysis of the suberin fraction of wax-free cork. With this method, hydrolysis of esters together with methylation of carboxylic and hydroxylic groups was observed. Mostly long chain aliphatic components, such as alkanols, alkanoic acids, v-hydroxyacids, v,v-alkanoic diacids, and several 9,10-epoxy and 9,10-dihydroxy forms have been found in keeping with results of other workers in the ﬁeld. Two other components that may give a more complete view of the architecture of suberin were also found, namely the phenolic compound ferulic acid, and glycerol which is probably esteriﬁed to carboxylic groups of the aliphatic building units of suberin
Keywords: Cork; pyrolysis mass spectrometry; Quercus suber; suberin; thermally assisted methylation

Influence of raw-material quality and process parameters in the production of insulation cork agglomerates - Pereira, H.; Baptista, C. (European Journal of Wood and Wood Products, 1993)
{Insulation cork agglomerates are produced with different low-cost raw-materials unsuitable for other products: virgin corks (from prunmgs, thinnings anti dead trees), reproduction corks (refuse and underaged) and industrial byproducts (corkback strips). These materials were analysed in relation to chemical composition, struc- ture and trituration behaviour. The industrial byproducts diffcr significantly from the other materials due to the presence of an important amount of the unsubcriscd lignocellulosic phlocm (the back of the corkboards) in a way that is detrimental to the agglomeration process. The influence of raw-material, granulometry and process parameters (time, temperature and pressure} were studied using an experimental autoclave. Temperature is the deter- mining factor for agglomeration. Insufficient adhesion is obtained under 230 ~C and adequate agglomeration is attained only with temperatures in the range 230 300 "C. corresponding to inass losses of 10 25%.
Keywords: chemical composition; CORK AGGLOMERATES; Raw materials; structure; trituration behaviour (Voyant)

A mass spectrometry study of thermal dissociation of cork - Filomena Bento, M.; Aurea Cunha, M.; Moutinho, A. M. C.; Pereira, H.; FORTES, M. A. (International Journal of Mass Spectrometry and Ion Processes, 1992)
Mass spectrometry has proved a convenient technique for the analysis of plant cell-wall material. In this work a comparative study is made of chemically treated cork and untreated cork, applying a method in which samples were continuously heated in vacuum. The outgassing products, upon electron-induced fragmentation, are analysed by a quadrupole mass spectrometer. Sequence of spectra at increasing temperatures were obtained for each sample, which allowed identification of the main groups of fragmentation. From such sequences of spectra one may derive intensity—temperature curves for each peak. Analysis of these curves for samples subjected to different treatments proved useful to identify the peaks, to assign the component which originates the species and even to derive activation energies.
Keywords: Cork; electron-induced fragmentation; thermal dissociation